Ray Eber Brown papers - Brown, Ray Eber, 1892-1962.
Correspondence, memoranda, diaries, writings, reports, articles, notebooks, specification sheets, subject files, newspaper clippings, printed matter, blueprints, charts, graphs, photographs, and other papers pertaining primarily to Brown's career in the U.S. Navy Dept. Bureau of Aeronautics, later the U.S. Dept. of the Navy Bureau of Aeronautics, as a naval architect and marine engineer. Subjects include the study of airships, cryogenics, and the uses of helium gas. Includes material pertaining to Brown's personal affairs. Correspondents include Garland Fulton and Charles E. Rosendahl.
Naval architect and engineer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Fulton, Garland, -- 1890-1974 -- Correspondence; Rosendahl, Charles E. -- 1892-1977 -- Correspondence; United States. -- Department of the Navy. -- Bureau of Aeronautics; United States. -- Navy Department. -- Bureau of Aeronautics; Aeronautics, Military -- United States; Airships; Helium; Low temperature engineering; Marine engineering; Naval architecture; Engineers; Naval architects